Plans of protection tasks for Natura 2000 areas and local spatial policy - Maciej J. Nowak; Paulina Legutko-Kobus (Acta Iuris Stetinensis, 2020)
The aim of the paper is to define the key spatial conflicts regarding planning relations be- tween the plans of protection tasks for Natura 2000 areas and local tools of spatial policy. The contents of all administrative court’s decisions related directly to the plans of protection tasks for Natura 2000 areas are analysed. The judgements issued in 2010 - 2019 are taken into account. Sixteen of such judgements have been distinguished in the Central Database of Judicial Decisions of the Supreme Administrative Court (in principle, grouping all of such rulings). They are classified, and the allegations made in the cases, as well as the contents of specific plans of protection tasks, are analysed. A quantitative and qualitative analysis of the contents of the judicial decisions is conducted. Based on the analyses carried out, two main conclusions can be drawn up: - on the occasion of spatial conflicts pending before administrative courts, related to the contents of plans of protection tasks for Natura 2000 areas, space users, as a rule, submit very similar objections to those concerning the direct tools of spatial policy; - the contents of plans of protection tasks directly related to the contents of spatial policy tools are very often underdefined both in subjective and formal terms.